The Effect of Employee Competence on Increasing Employee Motivation in Sumut Bank of Sharia Unit, North Sumatera - Nur M Ridha Tarigan; Heru Setiawan (Budapest International Research and Critics University, 2020)
This study aims to analyze the effect of employee competence on increasing employee motivation in Sumut Bank of Sharia Unit, North Sumatera. This research uses descriptive and verification methods. The place of research was conducted at Sumut Bank of Sharia Unit, North Sumatera. Considering the nature of this research is descriptive and verification, the research method used is descriptive survey and explanatory survey method. The type of investigation in this research is causality, which is testing the causal relationship between independent variables, intervening variables, moderating variables and dependent variables. The unit of analysis in this study is the employees at Sumut Bank of Sharia Unit, North Sumatera. The result shows that Competence in Sumut Bank of Sharia Unit, North Sumatera is perceived as poor to good. The highest average value is an indicator of the ability of employees to express narratives, meaning that employees actually have the ability to carry out their duties but are still not optimal. Nevertheless there are still some weaknesses in the indicator of the ability of employees to holistically look at problems in their lives. The experts also agree with the findings of researchers, and said competence still dominates important factors in the banking business, even sharia bank employees need to have special competencies.